Development of STEM-Based Electronic Student Worksheets in Physics on the Topic of Elasticity and Hooke's Law - Hasanah, Daimul; Budhi, Widodo (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to develop a STEM-Based Electronic Student Worksheet (E-LKPD) in Physics on the topic of Elasticity and Hooke's Law for Grade XI students of SMA Negeri 1 Sedayu, to determine the feasibility of the E-LKPD, and to assess student responses to the E-LKPD. This research falls under the category of Research and Development (R&D), following a modified version of the development model by Sugiyono, which is adapted into five stages: potential and problems; gathering information; product design; product validation; and product revision. The instruments used include an E-LKPD feasibility assessment questionnaire and a student response questionnaire regarding the E-LKPD. The data analysis techniques employed were the Aiken's V index analysis and descriptive statistics (percentage frequency). The results of this research are as follows: a STEM-based E-LKPD in Physics on the topic of Elasticity and Hooke's Law for Grade XI students of SMA Negeri 1 Sedayu has been developed in Anyflip format; the feasibility of the E-LKPD received a score of 0.93, which falls into the high category; and the student response to the Physics E-LKPD was 83%, which falls into the very high category. It can be concluded that the STEM-based E-LKPD in Physics on the topic of Elasticity and Hooke's Law for Grade XI students of SMA Negeri 1 Sedayu is suitable for use as a teaching material in physics learning.